Uterine Transplantation - E.THENMOZHI (International Journal of Pharma and Bio Sciences, 2017)
Womb transfer / uterine transfer is a surgical procedure whereby a healthy uterus is transplanted into an organism of which the uterus is absent or diseased. Several parts of the world tried uterine transplant but first successful pregnancy and delivery was conducted in Sweden. The Montreal Criteria are a set of criteria deemed to be required for the ethical execution of the uterine transplant in humans. These findings were presented at the International Federation of Gynaecology and Obstetrics' 20th World Congress in Rome in October 2012. It will be of utmost importance to continue to develop and improve protocols for psychology with thorough assessment and support in a systematic and structured way. For womb transplants the hospital has been preparing over the past few months and recipients were made to undergo ovulation stimulation through IVF. Frozen embryos are implanted in the womb after transplantation for the couple to conceive. The success of the transplant can be assessed after a month when recipient will undergo sonography and other tests to ensure the fitted uterus is functioning properly or not. The victim will undergo three major surgeries and the immunosuppression is given throughout life until hysterectomy is done.